PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS CANVA PADA MATA KULIAH FISIKA TEKNIK - Pakpahan, Rini Anggraini; Hasibuan, Erwina Azizah; Abidin, Jainal; Julianto, Julianto (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
The teaching and learning activity is a very important role in education because it involves the process of transferring knowledge, both at the basic and higher education levels. Efforts to instill understanding for students can be done by using modules, various learning models, and learning media. In the current digital era, there are various visual applications that can be utilized as learning media, one of which is Canva. Canva-based learning media was developed in this research for the Engineering Physics course. This research is R D type with 4D model. This research was held on first semester students of the Computer Science study program in Graha Nusantara University Padangsidimpuan in year 2023/2024.Â Validation sheet instrument was used to collect data. The collected assessment results are converted to a Likert scale. The results from the validator show 84% for material validation and 81% for media validation, both of which are included in the valid criteria. Thus, Canva-based learning media is feasible to using in Engineering Physics courses in force and motion subject.